Novel interpenetrating polymer network provides significant and long‐lasting improvements in hydration to the skin from different body areas. (9th September 2019) - Falla, Timothy; Rodan, Katie; Fields, Kathy; Bianchini, Robert; Mahon, Cullin; Skobowiat, Cezary
Abstract: Background: Hydration and moisturization both impact skin quality, directly reflecting its appearance. Signs and onset of dehydration‐related skin aging are region‐specific and require tailored treatment to be effective. Aims: To test the hydrating effects of formulas containing a novel 3‐dimensional 3‐polymer interpenetrating network (3D3P‐IPN) to deliver humectants and actives to specific body sites. Methods: Two clinical studies were conducted focused on the skin under eyes and body (arms/legs). Healthy women ages 25‐65 (eyes) or 35‐65 (body) with mild to moderate dry and aged skin were enrolled. Study product containing the 3D3P‐IPN and tailored actives was applied twice daily for 8 weeks on the periorbital area and for 4 weeks on the body. Changes in skin attributes were measured by biophysical instrumentation for hydration, dark circles, skin color, elasticity and transepidermal water loss, and by clinical grading and subject self‐assessment. Results: Significant improvements in hydration and skin smoothing were demonstrated in both studies. In the periorbital region, actives and humectants delivered by the 3D3P‐IPN also led to significant improvements in dark circles, fine lines/crow's feet, puffiness, restoring radiance, and overall younger‐looking appearance. On the arms and legs, there were significant reductions in crepiness and dullness. The arms and legs also had improvements in tactile and visual skin texture, radiance, and general healthy look. Improvements were immediate and persisted through the end of both studies. Conclusion: The 3D3P‐IPN provides immediate and long‐lasting improvements in skin hydration and overall healthy appearance regardless of the targeted application site.